The Volumetric Performance Analysis and Rutting of PG76 Asphalt Mixture with Fly ash as Filler: Volumetric Performance Analysis and Rutting of PG76 Asphalt Mixture with Fly ash as Filler - H. F. Tambunan; B. C. Marina; B. H. Sipayung (Journal of Engineering and Scientific Research, 2026)
Hot asphalt mixture is a type of pavement that is often used in a variety of traffic conditions and diverse environments. Permanent deformation in hot asphalt mixtures is damage caused by ambient temperature, aggregate quality and binding materials. This study shows the effect of using different types of binding materials, asphalt pen 60/70 and asphalt Pg76 with fly ash additives by analyzing the volumetric characteristics and rutting performance of asphalt mixtures. The results showed that the Pg76 mixture had a lower KAO value (6.5%) compared to the 60/70 pen mixture (6.6%). Based on volumetric analysis, the addition of fly ash as a filler has different effects depending on the type of asphalt used, which can be seen from the correlation values of VIM, VMA and VFB >0.7. The stability of the marshall in the PG76 FA mixture has a value of 1686.04 kg and the Pen 60/70 FA of 1407.58 kg. The addition of FA to hot asphalt mixtures can reduce moisture damage with an IRS value of more than 90%. The rutting performance of the PG76 FA mixture has better performance as evidenced by its higher dynamic stability values and lower deformation rate than the Pen 60/70 FA mixture. Temperature has a significant influence on the rutting performance of both mixtures especially in the Pen 60/70 FA mixture. The higher the test temperature indicates the greater the total deformation value, higher deformation rate, and lower dynamic stability in both mixtures.